AFIKSASI DALAM ALBUM UP ALL NIGHT DARI ONE DIRECTION - MUSA, MELLY CRISTINE (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
The study entitled â€œAffixation in the Album Up All Night by One Directionâ€. This study emphasizes the inflectional affixes and the derivational affixes in the lyrics of that album Up All Night. The method of this investigation is descriptive in the data are collected, analyzed using the method suggested by Nida and Oâ€™Grady and Dobrovolsky. Theoretically, this study is intended to contribution to the linguistics on morphology. Practically, this study helps the students or readers to know more the kinds of affixation on the album Up All Night so that they can understand. The result of this research shows that the inflectional affixes are plural {-s} and possessive {-â€˜s}, inflected to verbs: third person singular nouns-pas {-es}, present progressive {-ing}, past tense {-ed} and past participle {-en/ed} and inflected to adjectives: comparative {-er} and superlative {-est}. The derivational affixes are which consist of prefixes and suffixes. The prefixes are {in-}, {re-}, {im-}, and {super-}. While the suffixes are {-ly}, {-ful}, {-ing}, {-ed}, {-less}, {-ish}, {-ize}, {-ment} and each of them has their own function and meaning. Keyword: Affixation, Inflectional Affix, Derivational Affix, Prefix, Suffix, Album Up All Night by One Direction.